Consumer preferences matter for transforming food systems for sustainable healthy diets: Evidence from rural Bangladesh - Ecker, Olivier; Comstock, Andrew R.; de Brauw, Alan; Diao, Xinshen; Talukder, Md. Ruhul Amin (International Food Policy Research Institute, 2024)
Food system transformation strategies rely on consumer demand response for achieving sustainable healthy diets, but food consumption patterns and consumer preferences are often not well understood in many countries of the global South. This brief examines consumer demand in Bangladesh, a country in the take-off stage of agrifood system transformation, that has experienced improvements in diet quality but also an increasing incidence of overweight, with faster increases in rural than urban areas. The authors estimate responses in consumer demand to changes in incomes and changes in food prices, finding that rural consumer demand is driven by strong preferences for animal-source foods, while the demand for sugar and highly processed foods increases faster than total food demand when income rises. They conclude that agricultural value chain development can be an important policy instrument for improving household diet quality but can also lead to undesirable dietary change if food consumption incentives conflict with nutritional needs.